Strange magic [videorecording (DVD)] - Rydstrom, Gary; Lucas, George, 1944-; Cumming, Alan, 1965-; Wood, Evan Rachel, 1987-; Kelley, Elijah; Chenoweth, Kristin (Touchstone Home Entertainment, 2015)
A music-filled fairy tale about finding true love in the unlikeliest of places. Features a host of colorful characters, including a princess who has sworn off love, a dubious villain, a slightly nutty Sugar Plum Fairy, a tenacious elf, a mischievous imp, and a knight who is no Prince Charming.